2020
DOI: 10.1177/1179551420910122
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of the FreeStyle Libre Flash Glucose Monitoring System: The Experience of Young Patients With Type 1 Diabetes

Abstract: Background: In the current era of modern technology, the development of smart devices such as the flash glucose monitoring (FGM) systems helps patients with diabetes to effortlessly monitor their glucose levels more frequently. In this study, we determine the user acceptability of FGM among young patients with type 1 diabetes (T1D). Methods: A cross-sectional study was performed among 67 young patients with T1D in the age group of 13 to 19 years and who were managed on the FGM method for self-testing the gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…As T1D is a chronic disease and life-long therapy is needed, it is important for technology to be user-friendly without debilitating effects on the quality of daily living, which in term allows for high device uptake. As observed in other studies, [27][28][29] device acceptance was high as seen by unambiguous scores on system utilization and self-reported satisfaction. They preferred isCGM over capillary glucose tests, however, more than half of participants reported problems with the device.…”
Section: Self-reported Adverse Events and Complaints With Iscgmsupporting
confidence: 85%
“…As T1D is a chronic disease and life-long therapy is needed, it is important for technology to be user-friendly without debilitating effects on the quality of daily living, which in term allows for high device uptake. As observed in other studies, [27][28][29] device acceptance was high as seen by unambiguous scores on system utilization and self-reported satisfaction. They preferred isCGM over capillary glucose tests, however, more than half of participants reported problems with the device.…”
Section: Self-reported Adverse Events and Complaints With Iscgmsupporting
confidence: 85%
“…It is also important to consider factors other than blood glucose outcomes when evaluating the benefits of FM in this group, such as quality of life. Indeed, qualitative studies [ 29 , 30 ] have suggested such improvements in this demographic. Al Hayek et al [ 31 ] also found a significant reduction in diabetes distress in a sample of 187 adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more studies in the paediatric population should be conducted [ 43 ] to determine the long-term impact of using FGM on physiological and psychological aspects in adolescents and young adults [ 6 ]. Considering that the use of FGM is not allowed in people younger than 18 years in some countries [ 7 ], more research in this specific age group may help to modify this policy if its use results are shown to be beneficial, as different studies have reported on the families of children with diabetes [ 29 , 44 ].…”
Section: Discussionmentioning
confidence: 99%